(untitled) (Scientific journal of the Fergana State University, 2024)
This article studies the species composition and biomass of the pond biocenosis in the fish farm of Ziyo-Nemat Rivodzhi LLC in the Kuva district of the Fergana region. Therefore, after studying the influence of environmental factors on the increase in the biomass of pond biocenoses, the productivity of carp and silver carp grown in the pond in 2022-2024 was analyzed and compared in the autumn and spring seasons. Depending on seasonal factors, fish development in our conditions was 6% in April, 30-35% in July-August and 10-15% in September-October. According to the observation results, the maximum period of development of fish fry, that is, intensive growth, was observed in June, July and August. The development of pond biocenoses and their types is influenced by factors such as the physical properties of water, chemical composition, temperature, water transparency, the amount of oxygen dissolved in water, and nutrients. To increase the productivity of the pond biocenosis, it is necessary to properly carry out reclamation work. Important factors for this are improving hydrobiological and hydrochemical conditions and enriching the fish food supply.